The Impact of COVID-19 Infection on Oxygen Homeostasis: A Molecular Perspective - Alayash, Abdu I. (Frontiers in Physiology, 2021)
The novel coronavirus (2019-nCoV/SARS-CoV-2) causes respiratory symptoms that include a substantial pulmonary dysfunction with worsening arterial hypoxemia (low blood oxygenation), eventually leading to acute respiratory distress syndrome (ARDS). The impact of the viral infection on blood oxygenation and other elements of oxygen homeostasis, such as oxygen sensing and respiratory mitochondrial mechanisms, are not well understood. As a step towards understanding these mechanisms in the context of COVID-19, recent experiments revealed contradictory data on the impact of COVID19 infection on red blood cells (RBCs) oxygenation parameters. However, structural protein damage and membrane lipid remodeling in RBCs from COVID-19 patients that may impact RBC function have been reported. Moreover, COVID-19 infection could potentially disrupt one, if not all, of the other major pathways of homeostasis. Understanding the nature of the crosstalk between oxygen carrying, oxygen sensing (i.e., hypoxia inducible factor) proteins and the mitochondrial respiratory machinery may provide a target for therapeutic interventions.